INSTRUCTORS’ PERSPECTIVES ON ENGLISH LANGUAGE ACTIVITIES (ELA); AN AUTONOMOUS COMMUNICATIVE ENGLISH LANGUAGE LEARNING APPROACH FOR HIGHER LEARNING - Surinder Kaur Satwant Singh; Erda Wati Bakar; Afifah Quraishah Abdul Nasir (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The demands of the 21st century higher education environment and the global workplace has triggered a shift in the way English is taught. The Malaysian Ministry of Higher Education has introduced EcoELL (Ecosystem for English Language Learning) to meet this specific call especially towards producing learners who are competent and proficient in all reading, listening, speaking, and writing, with a focus on communicative abilities. The English Language Activities (ELA) is a pioneer project to assist students at higher education to have continuous engagement with the English Language beyond formal classroom. ELA focusses on students’ communication and presentation skills by affording them the opportunity to use the English language while completing ELA tasks in an informal and non-threatening setting. The preparation of ELA is guided and informed primarily by the principles of CEFR, that gives emphasis to communicative language tasks and placement of language learners as social agents. This study explores English language instructors’ outlook towards ELA implementation and their perceived impressions towards i) the benefits of ELA implementation, as well as ii) the challenges faced by instructors of its implementation at the National Defence University of Malaysia. By employing quantitative design, the study collected data from 23 English language instructors at the Language Centre through a questionnaire that was adapted from Lucas and Vicente (2022). The findings yielded positive responses as most instructors shared encouraging reactions towards the effectiveness of ELA in promoting effective autonomous communicative use of the English language outside classroom settings, along with several constructive feedback and suggestions from the instructors themselves to better regulate the management and implementation of ELA.